2020
DOI: 10.1371/journal.pone.0231466
|View full text |Cite
|
Sign up to set email alerts
|

DaHuangWan targets EGF signaling to inhibit the proliferation of hepatoma cells

Abstract: DaHuangWan (DHW) is a traditional herbal medicine used by Mongolian to treat liver cancer for many years. Clinical application of the drug has been shown to help control tumor progression, prolong survival and improve quality of life. However, the underlying mechanisms and side effects of this drug remain unclear, which greatly limits the clinical application and further optimization of DHW. In this study, we found that DHW inhibits the proliferation of hepatoma cells by modulating the epithelial growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Some researches revealed that Cos exerted anti-tumor activity by suppressing cell proliferation. One research indicated that Cos prevented the proliferation of liver cancer cells by regulating the signaling pathway of epithelial growth factor (EGF) ( Si et al, 2020 ). Another reported that Cos inhibited the proliferation, invasion, and metastasis of osteosarcoma by inhibiting the STAT3 signaling pathway ( Jin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some researches revealed that Cos exerted anti-tumor activity by suppressing cell proliferation. One research indicated that Cos prevented the proliferation of liver cancer cells by regulating the signaling pathway of epithelial growth factor (EGF) ( Si et al, 2020 ). Another reported that Cos inhibited the proliferation, invasion, and metastasis of osteosarcoma by inhibiting the STAT3 signaling pathway ( Jin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…89 A traditional herbal remedy, known as DaHuangWan, constituted of BBR and costunolide, suppresses the proliferation of hepatoma cells through modulating the epithelial growth factor (EGF) mechanism. 119 Moreover, BBR can hamper cell proliferation of HepG2, Hep3B, and SNU-182 via promoting protein expression of tumor suppressor genes, like activating transcription factor 3 (ATF3). 92…”
Section: Mechanistic Effects Of Bbr On Liver Cancermentioning
confidence: 99%
“…Additionally, the addition of delphinidin (a flavonoid) [ 58 ] and ginsenoside Rg3 [ 59 ] to the culture medium inhibited the EGFR/Akt/ERK signal axis in liver cancer cells. Da Huang Wan, a traditional herbal medicine, also decreased tumor progression in vitro by modulating EGF [ 60 ]. These results indicate that both HGF and EGF might exert their effects via the same signaling pathways i.e., Akt/ERK.…”
Section: Growth Factors In Liver Tumorigenesis and Liver Regenerationmentioning
confidence: 99%